Realization of drill rectifying control for coal shearer based on an improved PID algorithm - Ting Liu; Yuxin Du; Minming Tong; Dan Zhang (International Conference on Industrial Mechatronics and Automation (Online), 2016)
During the coal cutting process in mines, the drill stem is easy to be deflected in virtue of the complicated geological conditions. The deviation control of drill stems is of great significance for the production efficiency and service life of drill stems. Based on analyzing influence factors of the deflection of drills, this paper builds up a model to describe deflecting forces of the coal seam. Utilizing MPU6050, a three axis gyroscope, to get the deviation angles, an improved PID control algorithm is employed to guarantee directional drilling of the coal mining machine by applying electrohydraulic servo valves to rectify the deflective drill.